Voices from the pagan census : a national survey of witches and neo-pagans in the United States - Berger, Helen A., 1949-; Leach, Evan A.; Shaffer, Leigh S. (Studies in comparative religion (Columbia, S.C.), 2003)
"Voices from the Pagan Census provides unprecedented insight into the expanding but largely unstudied religious movement of Neo-Paganism in the United States. Helen A. Berger, Evan A. Leach, and Leigh S. Shaffer present findings of "The Pagan Census," which was created and distributed by Berger and Andras Corban Arthen of the Earthspirit Community. Analyzing the most comprehensive and largest-scale survey of Neo-Pagans to date, the authors offer a portrait of this emerging religious community, including an examination of Neo-Pagan political activism, educational achievements, family life, worship methods, experiences with the paranormal, and beliefs about such issues as life after death." "Keenly anticipated by the academic and Neo-Pagan communities, the results of the census provide the most in-depth information about the group yet assembled. Comparing Neo-Pagans with American society at large, Berger, Leach, and Shaffer show that although the two groups share certain statistical characteristics, there are differences as well. The scholars also identify variations within the Neo-Pagan population, including those related to geography and to the movement's multiple spiritual paths."--Jacket